The constitutional obligation of the State to establish tax exemptions in favor of persons with disabilities: analysis of the Constitutional Court of Ecuador judgment No. 019-17-SIN-CC - Erazo Galarza, Daniela Estefanía (2018)
This article is oriented to analyze the content of the court decision No. 019-17-SIN-CC, in which, the Constitutional Court resolved the petition of unconstitutionality filed against several tax norms, as a result of the petitioners plead this norms do not obey with the State's duty of establish tax exemptions in favor of people with disabilities as a priority attention group. In this decision, the Court decided to accept partially the petition filed, and also ordered to the National Assembly, within a period of one year, adapt the content of the Tax Reform Law and the Organic Code of Territorial Organization, Autonomy and Decentralization, in which it must include the tax exemptions that people with disabilities have the right to. Therefore, there are being analyzed the arguments that served as support for the Court to issue their court decision